Optimal modified tracking performance for MIMO systems under bandwidth constraint. (May 2016) - Sun, Xin-xiang; Wu, Jie; Zhan, Xi-Sheng; Han, Tao
Abstract: This paper investigates the optimal modified tracking performance of multi-input multi-output (MIMO) networked control systems (NCSs) with bandwidth and channel noise constraints. A new modified tracking performance index is proposed which prevents variations in the tracking error from leading to invalid data where there is no integrator in the plant. An expression for the optimal modified tracking performance is obtained using a method which includes co-prime factorization, partial factorization, spectral decomposition and H 2 norm. The obtained results show that the optimal modified tracking performance is influenced by the non-minimum phase (NMP) zeros, unstable poles, and their directions. Furthermore, the characteristics of the input signal, the modification factor, the bandwidth and the channel noise are also shown to be closely related to the optimal modified tracking performance. Finally, the efficiency of the result is verified using some typical examples. Abstract : Highlights: The optimal modified tracking performance for MIMO NCSs are given. The optimal performance with bandwidth constraint is obtained. The plant׳s internal structure and communication parameters depend on the performance. Two-parameter controllers can improve the tracking performance.